1988
DOI: 10.1159/000215868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Molecular-Weight Heparins on Laser-Induced Thrombus Formation in Rat Mesenteric Vessels

Abstract: Laser-induced thrombi have been frequently produced in rat mesenteric vessels to investigate the effect of antithrombotic drugs. We have tested low molecular heparins in comparison to unfractionated heparin. The investigations were carried out on male Wistar rats weighing 200–300 g; the animals were anesthetized with pentobarbital sodium (Nembu-tal®) 60 mg/kg i.p. Vascular lesions were induced with a Coherent CR-2 supergraphite ion laser (argon laser) mounted on a Leitz Orthoplan microscope. An intestinal loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
1
10
1
1
Order By: Relevance
“…For a 20-to 30-/xm-diameter mesenteric vessel, pulses of 120 mWx67 milliseconds were effective; one such pulse produced a small thrombus, and three to five repetitions at 1-minute intervals produced a thrombus that half-filled the vessel. 25 In our study, when electrocoagulation was used to produce a "permanent" block of blood flow in the MCA, it did not do so. With a maximal nonhemorrhagic electrocoagulation, we observed only a temporary occlusion, which lasted for less than 4 hours.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…For a 20-to 30-/xm-diameter mesenteric vessel, pulses of 120 mWx67 milliseconds were effective; one such pulse produced a small thrombus, and three to five repetitions at 1-minute intervals produced a thrombus that half-filled the vessel. 25 In our study, when electrocoagulation was used to produce a "permanent" block of blood flow in the MCA, it did not do so. With a maximal nonhemorrhagic electrocoagulation, we observed only a temporary occlusion, which lasted for less than 4 hours.…”
contrasting
confidence: 50%
“…24 Histological evaluation indicated that the endothelium was severely damaged by this procedure. 23 Lasers have also been used, both experimentally 25 and clinically 21 -26 ;ĉ ritical parameter, as in the neurosurgical studies, was found to be temperature. For a 20-to 30-/xm-diameter mesenteric vessel, pulses of 120 mWx67 milliseconds were effective; one such pulse produced a small thrombus, and three to five repetitions at 1-minute intervals produced a thrombus that half-filled the vessel.…”
mentioning
confidence: 99%
“…Comparison of the efficacy of the throm bin inhibitors studied with that of heparin revealed that much higher doses of heparin were necessary to obtain the same anti thrombotic effect in the 'rat model of laserinduced thrombosis' [25].…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments some SSH exerted a much stronger antithrombotic effect than their parent compounds, while the anticoagulant effects are equal or slightly higher [17][18][19]. Thus SSH because of their long-lasting antithrombotic effects might be well-suited to prevent thromboembolic episodes in highrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…A supersulfated LMWH (IK-SSH) has been developed by Iketon Farmaceutici, Milan and has been extensively tested in different animal toxicologic studies and in models of animal thrombosis [18][19][20]. We report here on a phase I clinical trial on the tolerance of IK-SSH and its effects on various hemostatic parameters in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%